2014
DOI: 10.2459/jcm.0b013e32835ec938
|View full text |Cite
|
Sign up to set email alerts
|

Association between preprocedural hemoglobin level and 1-year outcome of elective percutaneous coronary intervention

Abstract: The impact of anemia on the 12-month MACE was more prominent in patients with Hb below 10  mg/dl. Therefore, in patients with severe anemia listed for PCI, this level of Hb should be considered as a precaution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…Previous studies have reported conflicting data regarding the association between anaemia and clinical outcomes in patients undergoing PCI, with studies reporting both an independent association with increased mortality, MACE and major bleeding complications (3,5,(8)(9)(10)(15)(16)(17) or no increase in risk following adjustment for differences in age, comorbidity burden and procedural demographics (9,21,22), or only associated with poorer outcomes in patients with severe anaemia but not mild or moderate anaemia (11). Other studies have suggested that post-procedural anaemia is independently associated with MACE (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported conflicting data regarding the association between anaemia and clinical outcomes in patients undergoing PCI, with studies reporting both an independent association with increased mortality, MACE and major bleeding complications (3,5,(8)(9)(10)(15)(16)(17) or no increase in risk following adjustment for differences in age, comorbidity burden and procedural demographics (9,21,22), or only associated with poorer outcomes in patients with severe anaemia but not mild or moderate anaemia (11). Other studies have suggested that post-procedural anaemia is independently associated with MACE (23).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies suggest that whilst these relationships exists for unadjusted data, anaemia is no longer associated with increased mortality following adjustment for potential confounders such as age, comorbidity burden and procedural demographics, (16,(21)(22)(23), MACE (11,23)or ischemic complications (2). Other studies have also suggested an independent association with mortality only in males but not females (1).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Low albumin and hemoglobin levels could worsen the long‐term outcomes in patients with ACS through a mechanism related to inflammation and oxygen delivery. Previous studies also reported that hypoalbuminemia (<3.5 g/dL) and a low baseline hemoglobin level were independent predictors of long‐term outcomes for patients with myocardial infarction after PCI (Akirov et al, ; Hosseini et al, ; Wada et al, ). Most patients with ACS after PCI were hospitalized for no more than 3 days, as the critical process for ACS management was applied to them in general (Than et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…Long-term durability of surgical intervention on the right ventricular outflow tract (RVOT) for congenital heart disease (CHD) is highly variable, with allograft or bioprosthetic valves becoming dysfunctional and requiring further intervention over time (1). Transcatheter pulmonary valve implantation (TPVI) with the Melody® transcatheter pulmonary valve (TPV) (Medtronic Inc, Minneapolis, United States) has demonstrated good haemodynamic and clinical outcomes in the treatment of RVOT conduit dysfunction in patients with repaired CHD (2,3).…”
Section: Introductionmentioning
confidence: 99%